Tropical rhodolith beds are a major and belittled reef fish habitat - Moura, Rodrigo L.; Abieri, Maria L.; Castro, Guilherme M.; Carlos-Júnior, Lélis A.; Chiroque-Solano, Pamela M.; Fernandes, Nicole C.; Teixeira, Carolina D.; Ribeiro, Felipe V.; Salomon, Paulo S.; Freitas, Matheus O.; Gonçalves, Juliana T.; Neves, Leonardo M.; et al. (Scientific reports, 2021)
Understanding habitat-level variation in community structure provides an informed basis for natural resources’ management. Reef fishes are a major component of tropical marine biodiversity, but their abundance and distribution are poorly assessed beyond conventional SCUBA diving depths. Based on a baited-video survey of fish assemblages in Southwestern Atlantic’s most biodiverse region we show that species composition responded mainly to the two major hard-bottom megahabitats (reefs and rhodolith beds) and to the amount of light reaching the bottom. Both megahabitats encompassed typical reef fish assemblages but, unexpectedly, richness in rhodolith beds and reefs was equivalent. The dissimilar fish biomass and trophic structure in reefs and rhodolith beds indicates that these systems function based on contrasting energy pathways, such as the much lower herbivory recorded in the latter. Rhodolith beds, the dominant benthic megahabitat in the tropical Southwestern Atlantic shelf, play an underrated role as fish habitats, and it is critical that they are considered in conservation planning.